Kompensasi, Stres Kerja, Kepuasan Kerja dan Komitmen Organisasi - Norhayati Norhayati (Jurnal Manajemen dan Bisnis, 2021)
This research aims to determine and analyze the impact of compensation on organizational commitment, the impact of job stress on organizational commitment, the impact of job satisfaction on organizational commitment, and the role of job satisfaction as mediator the impact of compensation and job stress on organizational commitment.  This research  design is explanatory research. The population in this research are all temporary employees who had worked for more than 1 year amounting to 73 people. This research uses saturated sampling or census method as sampling technique. Partial Least Square with Smart PLS is used as data analysis.